Intracellular Oceanospirillales inhabit the gills of the hydrothermal vent snail Alviniconcha with chemosynthetic, γ‐Proteobacterial symbionts. Issue 6 (14th July 2014) - Beinart, R. A.; Nyholm, S. V.; Dubilier, N.; Girguis, P. R.
Summary Associations between bacteria from the γ‐Proteobacterial order Oceanospirillales and marine invertebrates are quite common. Members of the Oceanospirillales exhibit a diversity of interactions with their various hosts, ranging from the catabolism of complex compounds that benefit host growth to attacking and bursting host nuclei. Here, we describe the association between a novel Oceanospirillales phylotype and the hydrothermal vent snail Alviniconcha. Alviniconcha typically harbour chemoautotrophic γ‐ or ε‐Proteobacterial symbionts inside their gill cells. Via fluorescence in situ hybridization and transmission electron microscopy, we observed an Oceanospirillales phylotype (named AOP for 'Alviniconcha Oceanospirillales phylotype') in membrane‐bound vacuoles that were separate from the known γ‐ or ε‐Proteobacterial symbionts. Using quantitative polymerase chain reaction, we surveyed 181 Alviniconcha hosting γ‐Proteobacterial symbionts and 102 hosting ε‐Proteobacterial symbionts, and found that the population size of AOP was always minor relative to the canonical symbionts (median 0.53% of the total quantified 16S rRNA genes). Additionally, we detected AOP more frequently in Alviniconcha hosting γ‐Proteobacterial symbionts than in those hosting ε‐Proteobacterial symbionts (96% and 5% of individuals respectively). The high incidence of AOP in γ‐Proteobacteria hosting Alviniconcha implies that it could play a significant ecological role either as a host parasite or as an additional symbiont with unknown physiological capacities.